Caprine arthritis and encephalitis virus infection in goats of Bangladesh: Serological detection and its associated risk factors - Md. Habibur Rahma; Sonia Akther; Md. Shahin Alam; Md. Zulfekar Ali; Sadek Ahmed (Veterinary World, 2023)
Background and Aim: Caprine arthritis and encephalitis (CAE) is a multisystemic persistent viral disease of goat that causes significant economic losses to the farmers and livestock sector. However, no information in this country is available regarding CAE virus (CAEV) infection. Therefore, this study aimed to estimate the seroprevalence of CAEV infection among the goat population in the selected goat-prone districts in Bangladesh and to identify the associated risk factors of the disease.